If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 3(m + 4) Reorder the terms: 2 = 3(4 + m) 2 = (4 * 3 + m * 3) 2 = (12 + 3m) Solving 2 = 12 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 2 + -3m = 12 + 3m + -3m Combine like terms: 3m + -3m = 0 2 + -3m = 12 + 0 2 + -3m = 12 Add '-2' to each side of the equation. 2 + -2 + -3m = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -3m = 12 + -2 -3m = 12 + -2 Combine like terms: 12 + -2 = 10 -3m = 10 Divide each side by '-3'. m = -3.333333333 Simplifying m = -3.333333333
| 10x+50=150 | | y=4-4(2) | | y=4-4(1) | | 5-x=-10 | | y=4-4(0) | | y=4-4(-1) | | y=4-4(-2) | | -4+5y= | | x^4+4x^2+2x^2=0 | | x+2-5=4x+6 | | 8x+5=8(x+7) | | -3y-11=5y+13 | | 2x+30=4(x+8) | | -2(u+4)=-5u+7 | | 12x-7=24x+1 | | 25x-30x=125+500 | | -5(y+5)=1-4y | | x+2(x-1)=-8 | | 5x+10=7(x+2) | | 2x+2(x-1)=-8 | | 3(d+34)-14=45 | | x+x+1=x-1 | | x^2-34x=0 | | 16x-4=33 | | -x+29=-43 | | 2xy= | | (x-1)+4=17 | | 7-3(x-2)=(7-x)4-4x | | 7x-2x(5y-1)= | | 2-x^2+x=0 | | 15+17=13+14 | | -5(x-3)-7x=-36 |